Phase 1 study of pembrolizumab plus chemotherapy as first-line treatment in Japanese patients with advanced NSCLC. (2021) - Kurata, Takayasu; Nakagawa, Kazuhiko; Satouchi, Miyako; Seto, Takashi; Sawada, Takeshi; Han, Shirong; Homma, Masae; Noguchi, Kazuo; Nogami, Naoyuki
Highlights: We evaluated 1 L pembrolizumab+chemotherapy in Japanese patients with advanced NSCLC. Combination therapy was generally tolerable with no new safety signals. Antitumor activity was observed irrespective of histology and PD-L1 status. Results were consistent with those of global clinical trials. Abstract: Introduction: Pembrolizumab plus chemotherapy significantly improved outcomes over chemotherapy alone as first-line treatment in patients with advanced non–small-cell lung cancer (NSCLC) in phase 3 international trials. In the phase 1 KEYNOTE-011 study (parts B and C), we evaluated the safety/activity of pembrolizumab plus chemotherapy as first-line treatment in Japanese patients with advanced NSCLC. Methods: Eligible patients received 4 cycles (every 3 weeks) of pembrolizumab 200 mg plus chemotherapy (cisplatin 75 mg/m 2 /carboplatin area under the curve [AUC] 5 mg/mL/min and pemetrexed 500 mg/m 2 in part B [nonsquamous]; carboplatin AUC 6 mg/mL/min and paclitaxel 200 mg/m 2 /nab-paclitaxel 100 mg/m 2 (weekly) in part C [squamous]), followed by maintenance pembrolizumab (and pemetrexed, part B). The primary endpoint was incidence of dose-limiting toxicities (DLTs) during the first 3 weeks of treatment. Overall response rate (ORR; RECIST v1.1 by central review) was exploratory. Results: In part B (median follow-up, 16.0 months; n = 12) 1 DLT occurred (grade 4 hyponatremia). Grade ≥3 treatment-related adverse events (AEs) occurred in 9 patients (75%). Two patients had grade 5 treatment-related AEs (pneumonitis and interstitial lung disease). In part C (median follow-up, 9.9 months; n = 14), 2 DLTs occurred (both grade 3 febrile neutropenia). Grade ≥3 treatment-related AEs occurred in 11 patients (79%); none were fatal. ORR was 73% in part B and 50% in part C, irrespective of PD-L1 status. Conclusion: Safety results show first-line pembrolizumab plus chemotherapy is feasible in Japanese patients with advanced NSCLC. Antitumor activity was observed irrespective of PD-L1 status and was comparable to that in international studies. Trial register: ClinicalTrials.gov, NCT01840579